Micro-arc ignition on the oily surface of capacitively-coupled plasma - Kim, Yonghoon; Lee, Hunsu; Chang, Hongyoung (ELSEVIER SCIENCE BV, 2015)
Micro-arc ignition on the oily surface is investigated in a capacitively-coupled plasma (CCP) system. In this system, micro-arc generation is enhanced by increased level of plasma potential, which is induced by a DC-grounded coil between blocking capacitor and the powered electrode. The images of micro-arcs are captured with very short exposure time of 20 ms using intensified charge-coupled device triggered by a high speed comparator and the focused ground electrode is partially soiled with oil. The micro-arcs are observed only on the oily surface of the electrode. This observation provides that the oily surface of CCP is very weak for micro-arc ignition and micro-arc ignition is supposed to be enhanced by the oil evaporation and the thin oil layer, considering the RF Paschen breakdown of the oil vapor within the sheath and the dielectric breakdown of thin oil layer. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: ARGON GLOW-DISCHARGES; ELECTRICAL BREAKDOWN; PLANAR SYSTEM; RF; INITIATION; VACUUM; INCLUSIONS